Long non-coding RNA-dependent mechanism to regulate heme biosynthesis and erythrocyte development - Jinhua Liu (Nature Portfolio, 2018)
LncRNAs modulate diverse physiological cellular processes, however, their involvement in heme-dependent processes are not yet clear. Here the authors reveal the role of lncRNA UCA1 in erythroid cell development.